ASSESSMENT OF THE IMPACT OF IRRIGATION TECHNOLOGIES ON THE RECLAMATION STATUS OF LANDS UNDER THE CONDITIONS OF KHOREZM REGION (British Journal of Global Ecology and Sustainable Development, 2026)
The article presents the results of a scientific study conducted in the Khorezm region on the volume and mineralization of collector–drainage waters. The study evaluates the impact of implementing drip irrigation technology to reduce the formation of collector–drainage waters and examines the use of biological preparations to improve the reclamation status of irrigated lands. The findings provide insights into optimizing water use, improving soil conditions, and enhancing crop productivity under water-limited conditions.